G.S.T. – A Swot Analysis: Analyzing the Strengths, Weaknesses, Opportunities, and Threats of G.S.T. Implementation (Journal of Advances and Scholarly Researches in Allied Education, 2019)
After a long debate at national level, the Goods and Services Tax has been executed was implemented on dated July, 1 2017. The present paper examines the Strength, Weakness, Opportunity and Threat of this GST Tax, executed since its Implementation in the country. It has been observed from various reports and the articles, published during different successive periods that the reformed indirect taxation system has still there is wider scope of improvement in the coming years. However, the indirect tax system which was applicable on goods and services has been full of pitfalls and had a considerable regional disparity and lack of uniformity in this taxation system. Now after almost couple of years of its implementation, it becomes imperative to review this amended taxation system, in terms of its strength, weakness, opportunity and threat, so that a TQM, the Total Quality Management position may be attained in whole indirect taxation in the country.